Peran Guru dalam Pembentukan Karakter Peserta Didik - Nikmatulaili, Nikmatulaili; Rifma, Rifma; Syahril, Syahril (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
ABSTRACT This study aims to determine the role of the teacher in the formation of students in the 4.0 era. Descriptive descriptive research method. Data collection techniques using observation, observation, interviews and documentation. The results of the study show that the role of the teacher as an educator plays a very important role in the formation of the character of students. In addition, parents will also always support teachers in forming these characters because students will always spend their time at school rather than at home. Students communicate more with teachers than with their parents. In conclusion, the teacher plays an important role in the formation of the character of students, especially their role. Keywords: Teacher's Role, Character, students